Integrating communication skills into undergraduate science degrees: A practical and evidence-based approach - Mercer-Mapstone, Lucy D; Kuchel, Louise J (Teaching and Learning Inquiry, 2016)
The introduction of generic skills, such as communication, into undergraduate science degrees is becoming common in higher education and has met with mixed implementation success. This study designed, piloted, and evaluated a set of adaptable activities that scaffold the explicit teaching and learning of science communication with non-scientific audiences. These activities were implemented in undergraduate science classes from three disciplines at an Australian research-intensive university. A mixed- methods approach was used to evaluate learning gains by collecting data from: student surveys; semi-structured interviews with academic teaching staff; and student performance by marking of assessment tasks. Self-reported learning gains showed 95% of all students perceived improvements in their ability to do all communication skills and 94% perceived improvements in their confidence in communicating science as a result of the activities. Academic teaching staff reported improvements in students’ communication skills and understanding of core science content, and indicated that the tasks were explicit, engaging, and sustainable for use in future years. Students successfully transferred their learning to their assignments, demonstrating on average, a ‘good,’ ‘excellent,’ or ‘outstanding’ standard for each of the science communication criteria. These activities provide a promising starting point for integrating employable communication skills into undergraduate science degrees.